Uniform elementary fibrils in diverse plant cell walls - Kazuho Daicho; Shuji Fujisawa; Yoshinori Doi; Michio Suzuki; Junichiro Shiomi; Tsuguyuki Saito (Proceedings of the National Academy of Sciences, 2025)
Plant cell walls are composed of skeletal cellulose and a filling matrix of hemicelluloses and lignin. Cellulose has slender crystallite units referred to as microfibrils or elementary fibrils, and these crystallites form a dense network skeleton in the cell walls. In this study, we assessed the morphology and crystallinity of individually dispersed microfibrils isolated from the cell walls of wood, cotton, and ramie celluloses. It is well known that microfibrils in higher plants exhibit structural diversity, and these three plants, in particular, have distinct differences in the morphology and crystallinity of microfibrils. Our structural analyses combining atomic force microscopy (AFM), wide-angle X-ray diffraction (WAXD), small-angle X-ray scattering (SAXS), solid-state 13 C NMR spectroscopy, and all-atom molecular dynamics (MD) simulations revealed the uniformity in the cross-sectional dimensions and crystallinity of the dispersed microfibrils, irrespective of the plant species. The majority of the microfibrils were dispersed as structural units with widths of approximately 2 to 3 nm, and their crystallite sizes and crystallinity degrees were approximately 2 nm and 20%, respectively. These structural profiles were in agreement with the simulation results; here, the model assumed that a single microfibril consisted of 18 cellulose molecules. These results from the direct dimensional assessments support a recent hypothesis in biophysics that a single biosynthesis system of cellulose, referred to as the terminal complex (TC), consisted of 18 synthases. Some of the dispersed microfibrils had bundled sizes of two or three microfibrils. We also demonstrated that this bundling was stabilized by the fusion of several crystallites.